2013
DOI: 10.1016/j.neuron.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Induced Arc/Arg3.1 Primes CA1 Pyramidal Neurons for Metabotropic Glutamate Receptor-Dependent Long-Term Synaptic Depression

Abstract: SUMMARY A novel experience induces Arc/Arg3.1 gene as well as plasticity of CA1 neural networks. To understand how these are linked, we briefly exposed GFP reporter mice of Arc transcription to a novel environment. Excitatory synaptic function of CA1 neurons with recent in vivo Arc-induction (ArcGFP+) was similar to neighboring non-induced neurons (ArcGFP–). However, in response to group 1 mGluR activation, ArcGFP+ neurons preferentially displayed long-term synaptic depression (mGluR-LTD) and robust increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 39 publications
5
126
0
Order By: Relevance
“…Given the role of Arc in executing both rapid and more chronic forms of synaptic plasticity, an attractive model is that Arc protein levels are under continuous online regulation via regulated synthesis and degradation, the latter of which is controlled by Triad3A. These findings are supported by recent work, which demonstrates that Arc levels dictate the ability of a cell to elicit mGluR-LTD (Jakkamsetti et al, 2013). One prediction of this model is that alteration of Triad3A can trigger both immediate and longer-term effects on synaptic strength that will depend on ongoing synaptic activity, patterns of receptor activation, and homeostatic compensation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Given the role of Arc in executing both rapid and more chronic forms of synaptic plasticity, an attractive model is that Arc protein levels are under continuous online regulation via regulated synthesis and degradation, the latter of which is controlled by Triad3A. These findings are supported by recent work, which demonstrates that Arc levels dictate the ability of a cell to elicit mGluR-LTD (Jakkamsetti et al, 2013). One prediction of this model is that alteration of Triad3A can trigger both immediate and longer-term effects on synaptic strength that will depend on ongoing synaptic activity, patterns of receptor activation, and homeostatic compensation.…”
Section: Discussionmentioning
confidence: 84%
“…Arc is required for multiple forms of activity-dependent synaptic plasticity, including homeostatic scaling, hippocampal LTP, and protein synthesis-dependent LTD (Gao et al, 2010; Guzowski et al, 2000; Jakkamsetti et al, 2013; Rial Verde et al, 2006; Shepherd and Bear, 2011; Shepherd et al, 2006; Waung et al, 2008). In hippocampal neurons, overexpression of Triad3A mimicked and occluded TTX-induced upregulation as measured by surface expression of synaptic GluA1 (Figures 7A and 7B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevailing model is that group I mGluRs rapidly trigger the local synthesis of new dendritic proteins that are required for LTD by increasing the rate of AMPAR endocytosis at active synapses (Lü scher and Huber, 2010;Waung and Huber, 2009). Among the locally translated proteins are Arc/Arg3.1 (Jakkamsetti et al, 2013;Park et al, 2008;Waung et al, 2008), Map1b (Davidkova and Carroll, 2007), STEP1 (Zhang et al, 2008), and oligophrenin-1 (Nadif Kasri et al, 2011). Interestingly, different forms of intellectual disability (ID) have been linked to defective mGluR-LTD, confirming the tight regulation of AMPAR function at mature synapses through local protein synthesis as an essential form of plasticity and cognition (Aschrafi et al, 2005;Auerbach et al, 2011;Bateup et al, 2011;Lü scher and Huber, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Upon induction, Arc mRNA is known to be rapidly transported to dendrites where it is translated in response to pharmacological activation of Gp1 mGluRs (Steward et al, 1998, Park et al, 2008, Waung et al, 2008). Arc protein functions to weaken synaptic transmission by stimulating endocytosis of the postsynaptic AMPA-subtype of ionotropic glutamate receptors (Chowdhury et al, 2006) and is required for acute forms of synaptic weakening, such as long-term synaptic depression (LTD) (Park et al, 2008, Waung et al, 2008, Jakkamsetti et al, 2013), as well as homeostatic weakening of AMPAR-mediated synaptic currents in response to chronic increases in network activity (Shepherd et al, 2006, Shepherd and Bear, 2011). Very recent work revealed that Arc is necessary for the developmental pruning of climbing fiber axons onto cerebellar Purkinje neurons (Mikuni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%